2012
DOI: 10.1007/s00604-012-0809-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical detection of in situ DNA damage induced by enzyme-catalyzed Fenton reaction. Part II in hydrophobic room temperature ionic liquid

Abstract: A hydrophobic room temperature ionic liquid, 1-butyl-3-methylimidazolium hexafluorophosphate ([BMIM] [PF 6 ]), was applied as nonaqueous solvent for the generation of hydroxy radical (•OH) through glucose oxidasecatalyzed Fenton reaction. The enzyme catalyzes the oxidation of glucose, and the produced H 2 O 2 further reacts with transition metal ions, generating hydroxyl radicals. They attacked DNA and led its damage. This was detected by square wave voltammetry (SWV) of the electroactive indicator Co(bpy) 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…So the detection of DNA damage has got great importance. DNA damage can be caused by exogenous and endogenic factor such as UV and ionizing radiations, chemicals and reactive oxygen species (Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…So the detection of DNA damage has got great importance. DNA damage can be caused by exogenous and endogenic factor such as UV and ionizing radiations, chemicals and reactive oxygen species (Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The simulated values of R ct for K 3 [Fe(CN) 6 ]/ K 4 [Fe(CN) 6 ] at the bare GCE is 130.4 Ω. However, when polymerized ionic liquid film was deposited onto the glassy carbon electrode surface with controlling the potential step number at 4,8,12,16, and 20, the calculated charge transfer resistances were found to be 189.5, 307.6, 421.5, 1160, and 3805 Ω, respectively. The result indicates that the conductivity of the polymerized ionic liquid is not very well due that the charge transfer resistances were positively related to the film thickness.…”
Section: Resultsmentioning
confidence: 99%
“…They possess some excellent characteristics such as negligible vapor pressure, high thermal stability, good conductivity, etc. In recent years, ionic liquids have been extensively used in organic synthesis, separation approaches, nanomaterials, and sensors [1][2][3][4]. It has been demonstrated that ionic liquids can significantly improve the sensitivity and selectivity of electrochemical sensors [5,6].…”
Section: Introductionmentioning
confidence: 99%